Spatiotemporal Analysis of Urban Green Areas Using Change Detection: A Case Study of Kharkiv, Ukraine - Morar, Cezar; Lukić, Tin; Valjarević, Aleksandar; Niemets, Liudmyla; Kostrikov, Sergiy; Sehida, Kateryna; Telebienieva, Ievegeniia; Kliuchko, Liudmyla; Kobylin, Pavlo; Kravchenko, Kateryna (Frontiers in Environmental Science, 2022)
The contemporary globalized world characterizes significant concentration of urban population. Many socio-cultural, economic, environmental, and other problems of cities are exacerbated. It worsens the state of the urban environment and affects the health and population’s quality of life. UGAs are a part of the social space and a vital part of the urban landscape; they act as an environmental framework of the territory and a factor in ensuring a more comfortable environment of human life. This study aims at substantiating the importance of the UGAs, identifying the spatio-temporal dynamics of their functioning and transformational changes in their infrastructure given the expansion of the functions of the UGAs. The study was carried out on the example of the second city in Ukraine – Kharkiv. The authors substantiated and used an original combined approach to the usage of the urban remote sensing / GIS based on the changes detection to establish the contemporary state and monitor the spatial transformations of UGAs. We used a wide range of GIS platforms and online resources due to the lack of the digital cadastre for any thematic municipal area of Kharkiv. Therefore the results are unique and scientifically sound. The study analyzes the dynamics of the spatial and functional organization of the UGAs according to the Master Plans, plan-maps, and functional zoning of the city for 1867-2019. The peripheral UGAs became extremely important after the large-scale development of the extensive residential areas during the rapid industrial development in the city’s remote areas. They provide opportunities for population recreation near living places. Contemporary, the most infrastructural, comprehensively developed, and multidisciplinary are the central UGAs; the peripheral UGAs are developing gradually. Usage of GIS tools for the satellite images analysis during 2000-2020 allowed to identify the factors of the UGAs losses in Kharkiv and establish that UGAs were not expanding and partially shrinking during the study period. It is due to the intensive construction of the residential neighborhoods, primarily peripheral areas, infrastructure development, and expansion of the city transport network. The authors substantiated the change and expansion of the UGAs functions in accordance with the contemporary social demand.